A review on contamination and removal of sulfamethoxazole from aqueous solution using cleaner techniques: Present and future perspective. (20th March 2020) - Prasannamedha, G.; Kumar, P. Senthil
Abstract: Sulfamethoxazole is a persistent organic pollutant having N-amine and carboxyl groups rising from pharmaceutical industry. Upon consumption, it undergoes transformation reactions thereby leading to formation of oxidised, acetylated and hydrolysed metabolites in the environment. Though many countries banned use of sulfamethoxazole as growth promoters for veterinary, its occurrence in environment is witnessed even today in rivers, lakes, groundwater, sediments and ocean. This review provides thorough note on occurrence, destiny, toxicity effects and important materials involved in removal technologies like adsorption, Fenton/photo-Fenton process, electrochemical oxidation and photocatalytic degradation. SMX is removed via adsorption by formation of strong chemical interaction with functional moieties present in active sites of sorbents like hydrogen bonding, electrostatic interaction, π-π and hydrophobic interaction whereas AOP's use external energy, chemical agents for cleaving SMX structure through catalytic degradation by generation of hydroxyl radicals. Removal efficiency of material depends on experimental designs which rely on standard protocol. The article highlights the importance of sustainable development of technology by focussing on its feasibility and cost factor for building economic industrialization and statistics. It urge the significance of synergistic effects involved in nanocomposites/polymer in removing toxic contaminant via adsorption or photocatalytic degradation because of its high stability, functionality, ability to adapt at varying pH, sustainability and decreased cost in life cycle assessment. Graphical abstract: Image 1036797 Highlights: Identification of sulfamethoxazole as toxic waste in water. Removal mechanism of sulfamethoxazole is reviewed. Strategies involved in adsorption and oxidation process with respect to materials, feasibility are discussed. Importance of nanocomposites as an alternative is focussed in detail.